CAR‐Aptamers Enable Traceless Enrichment and Monitoring of CAR‐Positive Cells and Overcome Tumor Immune Escape - Hang Zhou; Tuersunayi Abudureheman; Wei‐Wei Zheng; Li‐Ting Yang; Jian‐Min Zhu; Ai‐Bin Liang; Cai‐Wen Duan; Kaiming Chen (Advanced Science, 2024)
Abstract Chimeric antigen receptor (CAR)‐positive cell therapy, specifically with anti‐CD19 CAR‐T (CAR19‐T) cells, achieves a high complete response during tumor treatment for hematological malignancies. Large‐scale production and application of CAR‐T therapy can be achieved by developing efficient and low‐cost enrichment methods for CAR‐T cells, expansion monitoring in vivo, and overcoming tumor escape. Here, novel CAR‐specific binding aptamers (CAR‐ap) to traceless sort CAR‐positive cells and obtain a high positive rate of CAR19‐T cells is identified. Additionally, CAR‐ap‐enriched CAR19‐T cells exhibit similar antitumor capacity as CAR‐ab (anti‐CAR antibody)‐enriched CAR‐T cells. Moreover, CAR‐ap accurately monitors the expansion of CAR19‐T cells in vivo and predicts the prognosis of CAR‐T treatment. Essentially, a novel class of stable CAR‐ap‐based bispecific circular aptamers (CAR‐bc‐ap) is constructed by linking CAR‐ap with a tumor surface antigen (TSA): protein tyrosine kinase 7 (PTK7) binding aptamer Sgc8. These CAR‐bc‐aps significantly enhance antitumor cytotoxicity with a loss of target antigens by retargeting CAR‐T cells to the tumor in vitro and in vivo. Overall, novel CAR‐aptamers are screened for traceless enrichment, monitoring of CAR‐positive cells, and overcoming tumor cell immune escape. This provides a low‐cost and high‐throughput approach for CAR‐positive cell‐based immunotherapy.